Acute effect of transcutaneous auricular vagus nerve stimulation on cardiac vagal activity in men living with HIV: A proof-of-concept clinical trial - Jason Azevedo de Medeiros; Uirassu Borges; Phelipe Wilde; Rafaela Catherine da Silva Cunha de Medeiros; Júlio César Medeiros Alves; Amon Gonçalves de Melo Neto; Jason R. Jaggers; Daniel Gomes da Silva Machado; Ronaldo Vagner Thomatieli dos Santos; Paulo Moreira Silva Dantas (PLoS ONE, 2025)
This proof-of-concept study evaluated the acute effects of transcutaneous auricular vagus nerve stimulation (taVNS) on cardiac vagal activity in people living with HIV. Twenty-one men living with HIV on antiretroviral therapy participated in a single-blind, crossover clinical trial. Participants underwent two counterbalanced stimulation conditions (taVNS and sham) with a 48-hour washout period. Cardiac vagal activity was assessed using vagally-mediated heart rate variability (vmHRV) indices, including the root mean square of successive differences (rMSSD) and the percentage of differences between adjacent normal intervals greater than 50 ms (pNN50), recorded before, during, and after stimulation. No significant changes in vmHRV parameters were observed over time or between conditions. These findings suggest that an acute taVNS session does not modulate cardiac vagal activity in people living with HIV. We discuss potential explanations for these results and highlight considerations for future research on taVNS as a non-pharmacological approach to autonomic modulation. Brazilian registry of clinical trials RBR-8k54cz.